IN PERCEPTUAL DEVELOPMENT RELATED TO CHILDREN RIGHTS APPLICATIONS OF CHILDREN COUNCIL - Erdem HAREKET (Fırat University, 2019)
The study aims to reveal the relationship between the perceptual improvement of students who are the members of Ankara Metropolitan Municipality Children Council about children rights and practices conducted in children council. There are 126 child participants as council members from the 2014-2015 period of Ankara Metropolitan Municipality Children Council in total. 68 of these children are female and 58 of them are male. In this study which was prepared with descriptive survey model, qualitative findings and quantitative findings about this subject were obtained from children who are member of children council in the direction of search problem. The study findings were obtained from children council perception survey which was prepared by researcher and has three parts with the part of personal information.Frequency and percent is figured up in order to describe demographic charactes of children who join the research. In the analysis of quantitative datas Kay-Kare test which is non-parametric test is used in order to determine the significance levels between given answers in the survey and variances SPSS 15.0 packaged software is used in process of statistic. Analysis of qualitative findings is conducted by content analysis method. When quantitative findings of the search is examined, it’s clear that answers given to some survey items, have showed meaningful difference in terms of gender, maternal education status, parental education status, school type and class level variables. When qualitative findings of the study is examined it’s clear that children council applications has effected positively to self-perception development about children rights, development of life skills and conceptual development through to children rights. Also some suggestions are submitted to practitioners and other researchers in the end of the study.